Timing of birth for women with a twin pregnancy at term: a randomised controlled trial - Haslam Ross R; Crowther Caroline A; Dodd Jodie M; Robinson Jeffrey S (BMC, 2010)
Abstract Background There is a well recognized risk of complications for both women and infants of a twin pregnancy, increasing beyond 37 weeks gestation. Preterm birth prior to 37 weeks gestation is a recognized complication of a twin pregnancy, however, up to 50% of twins will be born after this time. The aims of this randomised trial are to assess whether elective birth at 37 weeks gestation compared with standard care in women with a twin pregnancy affects the risk of perinatal death, and serious infant complications. Methods/Design Design: Multicentred randomised trial. Inclusion Criteria: women with a twin pregnancy at 366 weeks or more without contraindication to continuation of pregnancy. Trial Entry & Randomisation: Following written informed consent, eligible women will be randomised from 36+6 weeks gestation. The randomisation schedule uses balanced variable blocks, with stratification for centre of birth and planned mode of birth. Women will be randomised to either elective birth or standard care. Treatment Schedules: Women allocated to the elective birth group will be planned for elective birth from 37 weeks gestation. Where the plan is for vaginal birth, this will involve induction of labour. Where the plan is for caesarean birth, this will involve elective caesarean section. For women allocated to standard care, birth will be planned for 38 weeks gestation or later. Where the plan is for vaginal birth, this will involve either awaiting the spontaneous onset of labour, or induction of labour if required. Where the plan is for caesarean birth, this will involve elective caesarean section (after 38 and as close to 39 weeks as possible). Primary Study Outcome: A composite of perinatal mortality or serious neonatal morbidity. Sample Size: 460 women with a twin pregnancy to show a reduction in the composite outcome from 16.3% to 6.7% with adjustment for the clustering of twin infants within mothers (p = 0.05, 80% power). Discussion This is a protocol for a randomised trial, the findings of which will contribute information about the optimal time of birth for women with an uncomplicated multiple pregnancy at and beyond 37 weeks gestation. Clinical Trial Registration Current Controlled Trials ISRCTN15761056